The coastal community perspective of the mangrove ecosystem management in Karawang Regency, West Java, Indonesia - Nugraha Yan A. (EDP Sciences, 2021)
The development of coastal areas is growing rapidly in line with the high population growth that will threaten the continuity of coastal areas and ecosystems. Mangrove area located in the coastal area of Karawang Regency becomes an ecologically challenged area that greatly affects its sustainability. This study aims to examine mangrove ecosystems and community perspectives on the management of the mangrove ecosystems continuously and sustainably. The method used was a survey study at Nine Districts in Karawang Regency using the descriptive method with case study and perspective analysis on ten categories. Data were collected through interviews, observation and supported by secondary data. The description of this study was focused on mangrove ecosystem condition and community perspective in mangrove area management in coastal district Karawang. Data analysis used was a descriptive qualitative approach based on average with scales. The analysis results showed that most of the coastal communities in Karawang Regency strongly agree that; 1) The mangrove area in Karawang Regency is currently necessary/important to be managed to be sustainable, 2) The form of mangrove area management should involve all the local people, 3) There needs to be cooperation between the government and the local community in mangrove area management activities.